Tradition and Plants: Ethnobotany in the Perlon Unggahan Ritual of the Bonokeling Lineage Indigenous People - Fazriah, Ade Tias Nur; Hernawati, Diana; Fitriani, Rita (Biosfer: Jurnal Pendidikan Biologi, 2025)
The Bonokeling lineage, known in Indonesian as keturunan Bonokeling, is an indigenous community in Central Java, Indonesia, descended from Ki Bonokeling, a revered spiritual figure. They are known for preserving unique traditions and rituals that blend Javanese cultural values with Islamic teachings. One of their significant rituals is perlon unggahan, a ceremonial event held annually as a form of gratitude and preparation ahead of the fasting month of Ramadan. This study explores the tradition and the role of plants in the perlon unggahan ritual, focusing on their utilization and cultural significance. A qualitative research method with a phenomenological approach was employed, involving participatory observation, semi-structured in-depth interviews, documentation, and literature review. Data was collected from 11 informants selected through purposive sampling. The findings show that the ritual uses 39 plant species from 22 families. The Zingiberaceae family is the most frequently utilized. The most used plant parts are fruits, followed by leaves, stems, seeds, flowers, rhizomes, tubers, and sap. Among all the plants observed, krambil (Cocos nucifera L.) has the highest Species Use Value (SUV), which is highlighting its central role in the ritual. Plant use is categorized into three main functions: food, offerings, and ceremonial equipment. These findings underscore the importance of preserving both the cultural heritage and the biodiversity associated with this traditional ritual.